Simulation and study of an artificial ecosystem based on a cocoa plantation in Ghana, Africa - Palha, Catarina Ferreira Matos Quirino (2022)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science